Preparation method of nanoparticle-induced growth SiC nanowires and application thereof in medical materials

CN122586584BActive Publication Date: 2026-10-20XIAN MEDICAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611088729.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-20
Estimated Expiration
2046-07-22

AI Technical Summary

Benefits of technology

1、实现了无催化剂、无金属杂质的纯净SiC纳米线生长,保障了材料的生物相容性:本发明摒弃了传统催化剂辅助生长法中引入铁、镍等金属杂质的技术路线,采用纳米硅颗粒微氧化形成的SiO2@Si核壳结构作为硅源,通过自身反应生成SiO气体并与碳基体反应生成SiC纳米线。整个过程中无需添加任何金属催化剂,从根本上避免了金属离子残留对生物相容性的负面影响。所制得的SiC纳米线强韧化C/C复合材料不含细胞毒性或致炎性杂质,符合医用植入材料的严格生物学要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122586584B_ABST
    Figure CN122586584B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of SiC nanowires induced by nanoparticles and application of the SiC nanowires in medical materials, and belongs to the technical field of ceramic preparation. The preparation method comprises the following steps: firstly, performing micro-oxidation treatment on the surface of silicon nanoparticles to obtain SiO2-coated silicon nanoparticles; then, depositing a pyrolytic carbon layer on a carbon fiber preform through chemical vapor infiltration; then, vacuum impregnating the preform in a dispersion liquid of the SiO2-coated silicon nanoparticles; finally, performing heat treatment on the impregnated preform to obtain SiC nanowires induced by nanoparticles. In the application, the SiC nanowires are in-situ grown in the carbon fiber preform without adding other catalysts, and are uniformly distributed in the whole preform, so that the high toughening effect and the mechanical property stability of the medical C / C composite material are ensured, and the problems of introduction of catalyst impurities, complex process and poor uniformity in the existing SiC nanowire growth in the carbon fiber preform are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic preparation technology, specifically to a method for preparing SiC nanowires induced by nanoparticles and their application in medical materials. Background Technology

[0002] Carbon / carbon composites (C / C composites) have become ideal candidates for hard tissue repair materials such as artificial joints, bone fixation plates, and dental implants due to their excellent biocompatibility, corrosion resistance, low elastic modulus matching human bone, and outstanding wear resistance. Furthermore, C / C composites exhibit good chemical stability in physiological environments, effectively avoiding inflammatory responses induced by metal ion release; their excellent X-ray permeability also facilitates postoperative medical imaging monitoring. These properties endow C / C composites with significant development potential in the biomedical field, especially in the application of heavy-duty implants.

[0003] However, traditional C / C composites face significant challenges in terms of strength and toughness. On one hand, the interfacial bonding strength between the carbon matrix and carbon fibers is weak, making them prone to interfacial debonding and hindered fiber pull-out under complex physiological loads, resulting in low overall fracture toughness. On the other hand, the inherent brittleness of carbon materials makes them susceptible to sudden failure under impact loads or cyclic stresses, failing to meet the stringent requirements for fatigue resistance and damage tolerance in long-term implants. A single carbon fiber toughening mechanism is insufficient to construct a multi-scale three-dimensional network structure within the composite material, thus limiting further improvements in its mechanical properties.

[0004] To overcome the aforementioned mechanical bottlenecks, in-situ growth of silicon carbide nanowires (SiC nanowires, SiCNWs) within carbon fiber preforms has proven to be an efficient strengthening and toughening strategy in recent years. SiC nanowires possess ultra-high specific surface area, excellent mechanical properties, and good biocompatibility, enabling the construction of a three-dimensional network of nanoreinforcing frameworks within C / C composite matrices. Their bridging, pull-out, and crack deflection effects effectively dissipate fracture energy, significantly improving the flexural strength of the material. Simultaneously, SiC nanowires can regulate the interfacial bonding strength between the carbon matrix and fibers, preventing brittle fracture or delamination failure caused by excessively strong or weak interfaces. Furthermore, the introduction of these nanowires can improve cell adhesion and osseointegration properties, endowing C / C composites with enhanced bioactivity. Therefore, developing C / C composites strengthened and toughened by internally grown SiC nanowires has significant scientific and clinical translational value for overcoming the mechanical bottlenecks in their application in orthopedic and dental load-bearing implants.

[0005] Currently, the mainstream methods for growing SiC nanowires inside carbon fiber preforms include: (1) Catalyst-assisted growth method. This method has low equipment requirements, and the growth sites of nanowires can be designed by controlling the distribution of the catalyst. However, the catalyst metal impurities such as iron and nickel introduced by this method will damage the carbon fiber and affect the biocompatibility of C / C composite materials. (2) Chemical vapor infiltration / deposition method (CVI / CVD). This method is the most widely used and most mature technical route at present. It does not require metal catalysts, the product purity is high, and the damage to the fiber by the catalyst can be avoided. However, the precursor used in this method, trichloromethylsilane, is toxic and corrosive, has a high cost, and it is difficult to achieve uniform growth inside a thick preform. (3) Sol-gel method. This method also does not require metal catalysts. It uses the carbon fiber preform itself or deposited carbon as a carbon source, impregnates the preform with silica sol, and generates SiC nanowires through gelation, pyrolysis and high-temperature carbothermal reduction reaction. This method produces products with high purity and no metal impurities, but the process is complex (involving multiple steps such as sol preparation, impregnation, gelation, pyrolysis and high-temperature conversion). The cost of organosilicon precursors is relatively high, and the generated SiC nanowires are randomly distributed, which is not conducive to the densification of subsequent C / C composite materials and the stable control of mechanical properties.

[0006] In summary, current technologies for growing SiC nanowires inside carbon fiber preforms still have many shortcomings, significantly restricting the further application of C / C composites in the biomedical field. Therefore, how to achieve uniform and controllable preparation of SiC nanowires inside carbon fiber preforms under catalyst-free conditions, thereby effectively strengthening the mechanical properties of C / C composites, has become a key scientific problem that urgently needs to be solved. Summary of the Invention

[0007] To address the aforementioned technical problems, the present invention aims to provide a method for preparing SiC nanowires induced by nanoparticles and their application in medical materials, thereby solving the problems of catalyst impurity introduction, complex processes, and poor uniformity that exist in the existing in vivo growth of SiC nanowires from carbon fiber preforms.

[0008] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: In a first aspect, the present invention provides a method for preparing SiC nanowires by nanoparticle-induced growth, comprising the following steps: S1. Micro-oxidation treatment on the surface of nano-silicon particles: Silicon nanoparticles were micro-oxidized in a mixed atmosphere of argon and oxygen to obtain SiO2-coated silicon nanoparticles. S2. Pyrolytic carbon deposition of carbon fiber preforms: A carbon fiber preform with a deposited pyrolytic carbon layer is obtained by chemical vapor infiltration deposition of a pyrolytic carbon layer. S3. Vacuum impregnation introduces nanoparticles: The carbon fiber preform with the pyrolytic carbon layer deposited in S2 was vacuum impregnated in the dispersion of SiO2-coated silicon nanoparticles obtained in S1 to obtain a preform with nanoparticles introduced. S4, SiC nanowire growth: The preform of nanoparticles obtained from S3 was heat-treated in an inert atmosphere to obtain a preform of in-situ grown SiC nanowires on the carbon fiber surface, thus obtaining nanoparticle-induced SiC nanowires.

[0009] The beneficial effects of this invention are as follows: This invention achieves the growth of SiC nanowires inside a carbon fiber preform using only silicon nanoparticles as raw materials without adding other catalysts. A silicon dioxide layer is prepared on the surface of silicon nanoparticles through a micro-oxidation method to obtain a SiO2@Si core-shell structure. Using the SiO2@Si core-shell structure as a silicon source, SiO gas is generated through self-reaction and reacts with the carbon matrix to form SiC nanowires. This method avoids the negative impact of residual metal ions on biocompatibility, achieves uniform distribution of SiC nanowires within the carbon fiber preform, and significantly improves the strengthening and toughening effect and mechanical property stability.

[0010] Furthermore, the size of the silicon nanoparticles in S1 is 50-100 nm.

[0011] Furthermore, the total gas flow rate in S1 is 240-360 mL / min, and the flow rate ratio of argon to oxygen is (9-12):1.

[0012] Furthermore, the heating rate of the micro-oxidation treatment in S1 is 5-10℃ / min, the temperature of the micro-oxidation treatment is 600-800℃, and the holding time is 1-3 h.

[0013] The beneficial effects of adopting the above-mentioned further technical solution are as follows: The present invention prepares a silicon dioxide layer on the surface of silicon nanoparticles by micro-oxidation to form a SiO2@Si core-shell structure. The nanoparticles have high specific surface energy and can be effectively adsorbed on the surface of carbon fiber when impregnated with carbon fiber preform, inducing SiC nanowires to grow on the fiber surface.

[0014] Furthermore, the carbon fiber preform in S2 is a 2.5D needle-punched carbon fiber preform.

[0015] Furthermore, the conditions for chemical vapor infiltration in S2 are as follows: methane or propane is used as the carbon source gas, argon is used as the dilution gas, hydrogen is used as the carrier gas, the flow rate ratio of carbon source gas, dilution gas and carrier gas is (6-8):1:(0.2-0.4), and the total flow rate is 32-38 L / min.

[0016] Furthermore, the deposition temperature in S2 is 1000-1130℃, the deposition time is 4-8 h, and the deposition pressure is 10-30 kPa.

[0017] The beneficial effects of adopting the above-mentioned further technical solutions are as follows: the present invention prepares a pyrolytic carbon layer on the surface of the carbon fiber preform, which not only protects the fiber from damage by subsequent reactions, but also provides a carbon source for subsequent SiC growth.

[0018] Furthermore, the dispersion of SiO2-coated silicon nanoparticles in S3 includes SiO2-coated silicon nanoparticles, a dispersion medium, and a dispersant. The dispersion medium is anhydrous ethanol, the dispersant is polyvinylpyrrolidone, the concentration of the dispersion is 5-20 mg / mL, and the amount of dispersant added is 0.1%-0.5% of the total mass.

[0019] Furthermore, the dispersion of SiO2-coated silicon nanoparticles was prepared by dispersing SiO2-coated silicon nanoparticles in anhydrous ethanol, adding polyvinylpyrrolidone, magnetically stirring, and then ultrasonically treating.

[0020] Furthermore, the magnetic stirring speed is 300-500 rpm, and the stirring time is 1-2 hours.

[0021] Furthermore, the ultrasound power is 200-400 W, the frequency is 20-40 kHz, and the ultrasound duration is 40-60 min.

[0022] Furthermore, the impregnation pressure in S3 is 6-10 kPa, and the time is 20-40 min.

[0023] The beneficial effects of adopting the above-mentioned further technical solution are as follows: The present invention introduces nano-sized SiO2@Si core-shell particles into the carbon fiber preform through vacuum impregnation, which ensures the distribution and size uniformity of subsequent SiC nanowires in the carbon fiber preform.

[0024] Furthermore, after impregnation, the solvent is dried at room temperature for 12-24 hours to allow it to evaporate completely.

[0025] Furthermore, the heat treatment temperature in S4 is 1480-1560℃, and the holding time is 1-4 h.

[0026] The beneficial effects of adopting the above-mentioned further technical solution are as follows: During this heat treatment process, the nano-silicon in the SiO2@Si core-shell particles undergoes the following reaction with the external silicon dioxide layer through diffusion: Si + SiO₂ → 2SiO(g); The generated SiO gas escapes and undergoes a carbothermic reduction reaction with the surrounding carbon fiber surface or pyrolytic carbon layer, as follows: SiO(g) + 2C → SiC + CO(g); This allows for the induced growth of SiC nanowires on the carbon fiber surface, thereby achieving uniform preparation of SiC nanowires within the carbon fiber preform without a catalyst.

[0027] In a second aspect, the present invention provides nanoparticle-induced growth of SiC nanowires, which are prepared by the above-described preparation method.

[0028] The beneficial effects of the present invention are as follows: the nanoparticle-induced SiC nanowires prepared by the present invention grow in situ on the surface of carbon fiber and are uniformly distributed inside the preform, which can give full play to its multiple toughening mechanisms such as bridging, pull-out and crack deflection, and significantly improve the flexural strength of C / C composite material.

[0029] A third aspect of the present invention provides the application of the above-described nanoparticle-induced growth of SiC nanowires in the preparation of C / C composite materials.

[0030] In a fourth aspect, the present invention provides a method for preparing a nanoparticle-induced growth SiC nanowire-strengthened C / C composite material, wherein the preform of in-situ grown SiC nanowires on the carbon fiber surface obtained in S4 above is densified by pyrolysis of carbon through chemical vapor infiltration to obtain the nanoparticle-induced growth SiC nanowire-strengthened C / C composite material.

[0031] The beneficial effects of the present invention are as follows: The present invention achieves further densification by pyrolyzing and depositing carbon on a preform in which SiC nanowires are grown in situ on the surface of carbon fibers, and finally obtains a SiC nanowire-strengthened C / C composite material with no internal catalyst impurities, uniform distribution of SiC nanowires, and dense matrix.

[0032] Furthermore, the conditions for chemical vapor infiltration are as follows: methane or propane is used as the carbon source gas, argon is used as the dilution gas, hydrogen is used as the carrier gas, the flow rate ratio of carbon source gas, dilution gas and carrier gas is (6-8):1:(0.2-0.4), and the total flow rate is 8-24 L / min.

[0033] Furthermore, the deposition temperature was 1000-1080℃, the deposition pressure was 10-30 kPa, and the deposition time was 48-72 h.

[0034] In a fifth aspect, the present invention provides a nanoparticle-induced SiC nanowire-strengthened C / C composite material, which is prepared by the above-described preparation method.

[0035] The beneficial effects of the present invention are as follows: The nanoparticle-induced growth of SiC nanowires to strengthen the C / C composite material prepared by the present invention has a uniformly distributed three-dimensional network SiC nanowire structure inside and no metal catalyst is present, thus exhibiting excellent biocompatibility and mechanical properties.

[0036] In a sixth aspect, the present invention provides the application of the above-described nanoparticle-induced growth of SiC nanowires or nanoparticle-induced growth of SiC nanowires reinforced C / C composite materials in the preparation of medical materials.

[0037] The beneficial effects of this invention are as follows: the preparation method of SiC nanowires and the resulting C / C composite material do not introduce any metal catalysts and are free of cytotoxic or inflammatory impurities, meeting the stringent biological requirements for medical implant materials; simultaneously, the uniform distribution of SiC nanowires enhances the toughness and mechanical stability of the C / C composite material, ensuring its long-term mechanical reliability as a load-bearing implant; furthermore, the preparation process of this invention is simple, with low raw material costs, and the relevant parameters of SiC nanowires can be effectively controlled through process adjustments, thereby optimizing the mechanical properties and microstructure of the C / C composite material as needed. It possesses good process adaptability and product designability, and has broad application prospects in the field of medical materials.

[0038] The present invention has the following beneficial effects: 1. Achieving catalyst-free and metal-impurity-free pure SiC nanowire growth, ensuring the biocompatibility of the material: This invention abandons the technical route of introducing metal impurities such as iron and nickel in traditional catalyst-assisted growth methods. It uses a SiO2@Si core-shell structure formed by the micro-oxidation of nano-silicon particles as the silicon source, generating SiO gas through self-reaction and reacting with the carbon matrix to form SiC nanowires. No metal catalysts are added throughout the process, fundamentally avoiding the negative impact of residual metal ions on biocompatibility. The resulting SiC nanowire-strengthened C / C composite material is free of cytotoxic or inflammatory impurities, meeting the stringent biological requirements for medical implant materials.

[0039] 2. This method achieves uniform distribution of SiC nanowires within carbon fiber preforms, significantly improving the strengthening and toughening effect and mechanical property stability. It effectively solves the problems of limited penetration depth and uneven distribution in existing chemical vapor infiltration methods for thick preforms, and also avoids the disordered growth defects of nanowires in the sol-gel method. The uniformly distributed three-dimensional network of SiC nanowires can fully utilize its multiple toughening mechanisms, including bridging, pull-out, and crack deflection. Three-point bending performance tests show that the flexural strength of the C / C composite material prepared after SiC nanowire growth is increased by up to 60.2%, ensuring the long-term mechanical reliability of the material as a load-bearing implant.

[0040] 3. Simplified process, controllable cost, and excellent structural and performance designability: Compared with existing CVI / CVD methods that use toxic, corrosive, and expensive trichloromethylsilane precursors, and the complex multi-step process of sol-gel methods, this invention uses inexpensive nano-silicon powder as raw material and can generate SiC nanowires in situ inside the preform through only micro-oxidation, ultrasonic dispersion slurry preparation, vacuum impregnation, and a single high-temperature reaction. Subsequent pyrolytic carbon densification can be completed using conventional CVI processes. The overall process is significantly simplified, raw material costs are greatly reduced, and no toxic or harmful precursors are involved. Furthermore, by controlling the size of the nano-silicon particles, micro-oxidation temperature and time, impregnation concentration, and high-temperature reaction parameters (temperature, holding time, etc.), the diameter, aspect ratio, distribution density, and growth orientation of the SiC nanowires can be effectively controlled, thereby optimizing the mechanical properties and microstructure of the composite material as needed, exhibiting excellent process adaptability and product designability. Attached Figure Description

[0041] Figure 1 A schematic diagram of the preparation process for strengthening C / C composite materials by inducing the growth of SiC nanowires from nanoparticles; Figure 2 The XRD pattern of the silicon nanoparticles used in S1 in Example 1 is shown below. Figure 3 This is a spot scan of the energy spectrum of the silicon nanoparticles used in S1 in Example 1; Figure 4 The energy dispersive spectroscopy (EDS) pattern of the SiO2-coated silicon nanoparticles prepared in S1 of Example 1 is shown below. Figure 5 This is a spot scan of the energy spectrum of the SiC nanowires prepared in S4 of Example 1; Figure 6 This is a scanning electron microscope image of the in-situ grown SiC nanowires on the surface of the carbon fiber prepared in S4 of Example 1. Figure 7 This is a test diagram of the three-point bending test of the sample in Example 1; Figure 8 The images show the actual samples obtained in Examples 1-3 and Comparative Example 1 after the three-point bending test. Figure 9 The load-displacement curves of the C / C composite material prepared in Comparative Example 1 are shown. Figure 10 This is a load-displacement curve of the nanoparticle-induced SiC nanowire-strengthened C / C composite material prepared in Example 1. Figure 11 This is a load-displacement curve of the nanoparticle-induced growth of SiC nanowires to strengthen the C / C composite material prepared in Example 2. Figure 12The image shows the load-displacement curves of the nanoparticle-induced SiC nanowire-strengthened C / C composite material prepared in Example 3. Detailed Implementation

[0042] The principles and features of the present invention are described below with reference to the accompanying drawings. The examples given are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer should be followed. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0043] Example 1: A method for preparing nanoparticle-induced growth of SiC nanowires to strengthen C / C composite materials (see schematic diagram of the preparation process). Figure 1 (As shown), including the following steps: S1. Micro-oxidation treatment on the surface of nano-silicon particles: 50 nm silicon nanoparticles were selected and placed in a tube furnace for micro-oxidation under a mixed atmosphere of argon and oxygen. The total gas flow rate during micro-oxidation was 240 mL / min, and the argon-to-oxygen flow ratio was 9:1. The heating rate was controlled at 5 °C / min, the oxidation temperature was 600 °C, and the holding time was 1 h. A silicon dioxide layer was formed on the surface of the silicon nanoparticles, thus obtaining SiO2-coated silicon nanoparticles.

[0044] S2. Pyrolytic carbon deposition of carbon fiber preforms: A 2.5D needle-punched carbon fiber preform was placed in a chemical vapor infiltration furnace, using methane as the carbon source gas, argon as the dilution gas, and hydrogen as the carrier gas for pyrolytic carbon deposition. The flow ratio of methane, argon, and hydrogen was 6:1:0.2, and the total flow rate was 32 L / min. The deposition temperature was 1000℃, the deposition time was 4 h, and the deposition pressure was 10 kPa, resulting in the deposition of a thin and uniform pyrolytic carbon layer on the carbon fiber surface, thus obtaining the carbon fiber preform with the deposited pyrolytic carbon layer.

[0045] S3. Vacuum impregnation introduces nanoparticles: First, the SiO2-coated silicon nanoparticles obtained in S1 were dispersed in anhydrous ethanol, and the concentration of the dispersion was controlled at 5 mg / mL. Polyvinylpyrrolidone (PVP) was added as a dispersant at 0.1% of the total mass. Then, the mixture was magnetically stirred at 300 rpm for 1 h and ultrasonically dispersed at 200 W power and 20 kHz frequency for 40 min to obtain a uniform and stable dispersion. Next, the dispersion was poured into a vacuum impregnation chamber, and the carbon fiber preform with a deposited pyrolytic carbon layer obtained in S2 was placed in it. The chamber was evacuated to 6 kPa and impregnated for 20 min. After the gas inside the preform was discharged, the pressure was restored to normal. The pressure difference was used to allow the dispersion to fully penetrate the pores inside the preform. Finally, after impregnation, the preform was removed and dried at room temperature in a fume hood for 12 h to allow the solvent to evaporate completely, resulting in a preform with nanoparticles introduced.

[0046] Growth of S4 and SiC nanowires: The preform containing nanoparticles obtained in S3 was placed in a tube furnace and subjected to high-temperature heat treatment under an argon protective atmosphere. The argon flow rate was 200 mL / min, the SiC growth temperature was 1480℃, and the holding time was 1 h. After the reaction, the furnace was cooled to room temperature. During this process, the nano-silicon in the SiO2-coated silicon nanoparticles reacted with SiO2 to generate SiO gas. The SiO gas then underwent a carbothermic reduction reaction with the carbon fiber surface or the pyrolytic carbon layer, resulting in the in-situ growth of SiC nanowires on the carbon fiber surface.

[0047] S5, Densification of Pyrolytic Carbon: The carbon fiber preform with SiC nanowires grown in S4 was placed in a chemical vapor infiltration furnace for further densification of the pyrolytic carbon. The argon flow rate was 100 mL / min, and the heating rate was 5 °C / min. During deposition, methane was used as the carbon source gas, argon as the dilution gas, and hydrogen as the carrier gas. The flow ratio of methane, argon, and hydrogen was 6:1:0.2, the total flow rate was 8 L / min, the deposition temperature was 1000 °C, the deposition pressure was 10 kPa, and the deposition time was 48 h. Finally, a nanoparticle-induced SiC nanowire-strengthened C / C composite material with no internal catalyst impurities, uniform SiC nanowire distribution, and a dense matrix was obtained.

[0048] Example 2: A method for preparing nanoparticle-induced growth of SiC nanowires to strengthen C / C composite materials (see schematic diagram of the preparation process). Figure 1 (As shown), including the following steps: S1. Micro-oxidation treatment on the surface of nano-silicon particles: 75 nm silicon nanoparticles were selected and placed in a tube furnace for micro-oxidation under a mixed atmosphere of argon and oxygen. The total gas flow rate during micro-oxidation was 300 mL / min, and the argon-to-oxygen flow ratio was 10.5:1. The heating rate was controlled at 7.5 °C / min, the oxidation temperature was 700 °C, and the holding time was 2 h. A silicon dioxide layer was formed on the surface of the silicon nanoparticles, thus obtaining SiO2-coated silicon nanoparticles.

[0049] S2. Pyrolytic carbon deposition of carbon fiber preforms: A 2.5D needle-punched carbon fiber preform was placed in a chemical vapor infiltration furnace, using propane as the carbon source gas, argon as the dilution gas, and hydrogen as the carrier gas for pyrolytic carbon deposition. The flow ratio of propane, argon, and hydrogen was 7:1:0.3, and the total flow rate was 35 L / min. The deposition temperature was 1065℃, the deposition time was 6 h, and the deposition pressure was 20 kPa, resulting in the deposition of a thin and uniform pyrolytic carbon layer on the carbon fiber surface, thus obtaining the carbon fiber preform with the deposited pyrolytic carbon layer.

[0050] S3. Vacuum impregnation introduces nanoparticles: First, the SiO2-coated silicon nanoparticles obtained in S1 were dispersed in anhydrous ethanol, and the concentration of the dispersion was controlled at 12.5 mg / mL. Polyvinylpyrrolidone (PVP) was added as a dispersant at 0.3% of the total mass. Then, the mixture was magnetically stirred at 400 rpm for 1.5 h and ultrasonically dispersed at 300 W power and 30 kHz frequency for 50 min to obtain a uniform and stable dispersion. Next, the dispersion was poured into a vacuum impregnation chamber, and the carbon fiber preform with a deposited pyrolytic carbon layer obtained in S2 was placed inside. The chamber was evacuated to 8 kPa and impregnated for 30 min. After the gas inside the preform was discharged, the pressure was restored to normal. The pressure difference was used to allow the dispersion to fully penetrate the pores inside the preform. Finally, after impregnation, the preform was removed and dried at room temperature in a fume hood for 18 h to allow the solvent to evaporate completely, resulting in a preform with nanoparticles introduced.

[0051] Growth of S4 and SiC nanowires: The preform containing nanoparticles obtained in S3 was placed in a tube furnace and subjected to high-temperature heat treatment under an argon protective atmosphere. The argon flow rate was 300 mL / min, the SiC growth temperature was 1520℃, and the holding time was 2.5 h. After the reaction, the furnace was cooled to room temperature. During this process, the nano-silicon in the SiO2-coated silicon nanoparticles reacted with SiO2 to generate SiO gas. The SiO gas then underwent a carbothermic reduction reaction with the carbon fiber surface or the pyrolytic carbon layer, resulting in the in-situ growth of SiC nanowires on the carbon fiber surface.

[0052] S5, Densification of Pyrolytic Carbon: The carbon fiber preform with SiC nanowires grown in S4 was placed in a chemical vapor infiltration furnace for further densification of the pyrolytic carbon. The argon flow rate was 110 mL / min, and the heating rate was 7.5 °C / min. During deposition, propane was used as the carbon source gas, argon as the dilution gas, and hydrogen as the carrier gas. The flow ratio of propane, argon, and hydrogen was 7:1:0.3, the total flow rate was 16 L / min, the deposition temperature was 1040 °C, the deposition pressure was 20 kPa, and the deposition time was 60 h. Finally, a nanoparticle-induced SiC nanowire-strengthened C / C composite material with no internal catalyst impurities, uniform SiC nanowire distribution, and a dense matrix was obtained.

[0053] Example 3: A method for preparing nanoparticle-induced growth of SiC nanowires to strengthen C / C composite materials (see schematic diagram of the preparation process). Figure 1 (As shown), including the following steps: S1. Micro-oxidation treatment on the surface of nano-silicon particles: 100 nm silicon nanoparticles were selected and placed in a tube furnace for micro-oxidation under a mixed atmosphere of argon and oxygen. The total gas flow rate during micro-oxidation was 360 mL / min, and the argon-to-oxygen flow ratio was 12:1. The heating rate was controlled at 10 °C / min, the oxidation temperature was 800 °C, and the holding time was 3 h. A silicon dioxide layer was formed on the surface of the silicon nanoparticles, thus obtaining SiO2-coated silicon nanoparticles.

[0054] S2. Pyrolytic carbon deposition of carbon fiber preforms: A 2.5D needle-punched carbon fiber preform was placed in a chemical vapor infiltration furnace, using propane as the carbon source gas, argon as the dilution gas, and hydrogen as the carrier gas for pyrolytic carbon deposition. The flow ratio of propane, argon, and hydrogen was 8:1:0.4, and the total flow rate was 38 L / min. The deposition temperature was 1130℃, the deposition time was 8 h, and the deposition pressure was 30 kPa, resulting in the deposition of a thin and uniform pyrolytic carbon layer on the carbon fiber surface, thus obtaining the carbon fiber preform with the deposited pyrolytic carbon layer.

[0055] S3. Vacuum impregnation introduces nanoparticles: First, the SiO2-coated silicon nanoparticles obtained in S1 were dispersed in anhydrous ethanol, and the concentration of the dispersion was controlled at 20 mg / mL. Polyvinylpyrrolidone (PVP) was added as a dispersant at 0.5% of the total mass. Then, the mixture was magnetically stirred at 500 rpm for 2 h and ultrasonically dispersed at 400 W power and 40 kHz frequency for 60 min to obtain a uniform and stable dispersion. Next, the dispersion was poured into a vacuum impregnation chamber, and the carbon fiber preform with a deposited pyrolytic carbon layer obtained in S2 was placed inside. The chamber was evacuated to 10 kPa and impregnated for 40 min. After the gas inside the preform was discharged, the pressure was restored to normal. The pressure difference was used to allow the dispersion to fully penetrate the pores inside the preform. Finally, after impregnation, the preform was removed and dried at room temperature in a fume hood for 24 h to allow the solvent to evaporate completely, resulting in a preform with nanoparticles introduced.

[0056] Growth of S4 and SiC nanowires: The preform containing nanoparticles obtained in S3 was placed in a tube furnace and subjected to high-temperature heat treatment under an argon protective atmosphere. The argon flow rate was 400 mL / min, the SiC growth temperature was 1560℃, and the holding time was 4 h. After the reaction, the furnace was cooled to room temperature. During this process, the nano-silicon in the SiO2-coated silicon nanoparticles reacted with SiO2 to generate SiO gas. The SiO gas then underwent a carbothermic reduction reaction with the carbon fiber surface or the pyrolytic carbon layer, resulting in the in-situ growth of SiC nanowires on the carbon fiber surface.

[0057] S5, Densification of Pyrolytic Carbon: The carbon fiber preform with SiC nanowires grown in S4 was placed in a chemical vapor infiltration furnace for further densification of the pyrolytic carbon. The argon flow rate was 120 mL / min, and the heating rate was 10 °C / min. During deposition, propane was used as the carbon source gas, argon as the dilution gas, and hydrogen as the carrier gas. The flow ratio of propane, argon, and hydrogen was 8:1:0.4, the total flow rate was 24 L / min, the deposition temperature was 1080 °C, the deposition pressure was 30 kPa, and the deposition time was 72 h. Finally, a nanoparticle-induced SiC nanowire-strengthened C / C composite material with no internal catalyst impurities, uniform SiC nanowire distribution, and a dense matrix was obtained.

[0058] Comparative Example 1: A C / C composite material, the preparation method of which differs from that of Example 1, does not contain S1, and SiO2-coated silicon nanoparticles are not added to S3, while the remaining steps are the same as in Example 1.

[0059] Comparative Example 2: A C / C composite material, the preparation method of which differs from that of Example 2, does not contain S1, and SiO2-coated silicon nanoparticles are not added to S3, while the remaining steps are the same as in Example 2.

[0060] Comparative Example 3: A C / C composite material, the preparation method of which differs from that of Example 3, does not contain S1, and SiO2-coated silicon nanoparticles are not added in S3, while the remaining steps are the same as in Example 3.

[0061] Experimental Example 1: XRD Phase Analysis The silicon nanoparticles used as raw material were subjected to XRD phase analysis, and the results are as follows: Figure 2 As shown, its diffraction pattern matches the standard powder diffraction card PDF#27-1402 (silicon phase), indicating that the raw material used is elemental silicon and there are no other impurities.

[0062] Experimental Example 2: Energy Dispersive Spectroscopy (EDS) Analysis The C / C composite materials obtained in Examples 1-3 have basically the same characteristics. The following characterization is performed using Example 1 as an example: Energy dispersive spectroscopy (EDS) scans and measurements were performed on the silicon nanoparticles used in Example 1, the SiO2-coated silicon nanoparticles prepared in S1 of Example 1, and the SiC nanowires grown in S4 of Example 1. The results are as follows: Figures 3-5 As shown.

[0063] The results showed that SiO2 was formed on the surface of silicon nanoparticles after S1 treatment, and the product formed after S4 heat treatment was SiC.

[0064] Experimental Example 3: Scanning Electron Microscopy Characterization The C / C composite materials obtained in Examples 1-3 have basically the same characteristics. Below, using Example 1 as an example, we observe the preform with SiC nanowires grown in situ on the surface of the carbon fiber obtained in S4 of Example 1 using scanning electron microscopy. The results are as follows: Figure 6 As shown.

[0065] from Figure 6 It can be seen that after S4 treatment, SiC nanowires were successfully grown on the surface of the carbon fiber preform, and the grown nanowires were of uniform thickness and evenly distributed on the carbon fiber surface.

[0066] Test Example 4: Bending Performance Test Three-point bending tests were performed on the C / C composite materials prepared in Examples 1-3 and Comparative Examples 1-3, respectively.

[0067] According to the GB / T 40398.2-2021 standard for the flexural performance test of C / C composite materials, the three-point flexural performance of the composite material was tested using the three-point flexural test mode of a CMT5304-2kN electronic universal testing machine (the testing process is as follows). Figure 7(As shown). The specimen dimensions were 55 mm (±1 mm) × 10 mm (±0.5 mm) × 4 mm (±0.5 mm), and the specimen was cut in a direction parallel to the lamination direction of the non-woven fabric. The span of the three-point bending was 40 mm, the loading speed was 0.3 mm / min, and the radius of curvature of both the upper indenter and the fulcrum was 2 mm. During the loading process, the computer collected and recorded the load-displacement curves through sensors. The three-point bending strength was obtained using the following formula:

[0068] In the formula: σf is the three-point bending strength, in MPa; F is the maximum load, N; L is the span, in mm; h is the thickness of the sample, in mm; b is the width of the sample, in mm; The C / C composite materials prepared in Comparative Examples 1-3 have basically the same characteristics. The following analysis of bending failure behavior is based on Comparative Example 1: The actual images of the fractured objects after the three-point bending test of Examples 1-3 and Comparative Example 1 are shown below. Figure 8 As shown, the load-displacement correlation data during the three-point bending test of different materials are as follows: Figures 9-12 As shown in Table 1, the results of the three-point bending strength are as follows.

[0069] Table 1. Results of Three-Point Bending Strength Test

[0070] Depend on Figures 9-12 It can be seen that the C / C composite materials prepared by growing SiC nanowires on the surface of carbon fiber preforms in Examples 1-3 still exhibit their unique "pseudoplastic" fracture behavior. Table 1 shows that the three-point bending strength of the C / C material with SiC nanowire-strengthened surface on the carbon fiber preform prepared according to the process of the present invention is improved compared with the C / C composite material without SiC nanowire growth; among them, the sample of Example 1 after SiC nanowire strengthening can reach the highest three-point bending strength of 165 MPa, while the three-point bending strength of the unstrengthened C / C composite material is only 103 MPa. The three-point bending strength of the C / C composite material strengthened by the present invention is improved by 60.2%, and the mechanical properties are significantly improved.

[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing SiC nanowires induced by nanoparticle growth, characterized in that, Includes the following steps: S1. Micro-oxidation treatment on the surface of nano-silicon particles: Silicon nanoparticles were micro-oxidized in a mixed atmosphere of argon and oxygen to obtain SiO2-coated silicon nanoparticles. S2. Pyrolytic carbon deposition of carbon fiber preforms: A carbon fiber preform with a deposited pyrolytic carbon layer is obtained by chemical vapor infiltration deposition of a pyrolytic carbon layer. S3. Vacuum impregnation introduces nanoparticles: The carbon fiber preform with the pyrolytic carbon layer deposited in S2 was vacuum impregnated in the dispersion of SiO2-coated silicon nanoparticles obtained in S1 to obtain a preform with nanoparticles introduced. S4, SiC nanowire growth: The preform of nanoparticles obtained in S3 was heat-treated in an inert atmosphere to obtain a preform of SiC nanowires grown in situ on the carbon fiber surface, that is, the nanoparticle-induced growth of SiC nanowires was obtained. The silicon nanoparticles in S1 have a size of 50-100 nm. The total gas flow rate of the mixed atmosphere is 240-360 mL / min, and the flow rate ratio of argon to oxygen is (9-12):1; The heating rate of the micro-oxidation treatment is 5-10℃ / min, the temperature of the micro-oxidation treatment is 600-800℃, and the holding time is 1-3 h; The dispersion of SiO2-coated silicon nanoparticles in S3 includes SiO2-coated silicon nanoparticles, a dispersion medium, and a dispersant; the concentration of the dispersion is 5-20 mg / mL, and the amount of dispersant added is 0.1%-0.5% of the total mass of the dispersion. The heat treatment temperature in S4 is 1480-1560℃, and the holding time is 1-4 h.

2. The method for preparing SiC nanowires induced by nanoparticle growth according to claim 1, characterized in that, The conditions for chemical vapor infiltration in S2 are as follows: methane or propane is used as the carbon source gas, argon is used as the dilution gas, hydrogen is used as the carrier gas, the flow rate ratio of carbon source gas, dilution gas and carrier gas is (6-8):1:(0.2-0.4), and the total flow rate is 32-38 L / min. The deposition temperature was 1000-1130℃, the deposition time was 4-8 h, and the deposition pressure was 10-30 kPa.

3. The method for preparing SiC nanowires induced by nanoparticle growth according to claim 1, characterized in that, The dispersion medium in S3 is anhydrous ethanol, and the dispersant is polyvinylpyrrolidone. The impregnation pressure is 6-10 kPa and the time is 20-40 min.

4. A method for inducing the growth of SiC nanowires using nanoparticles, characterized in that, It is prepared by the preparation method according to any one of claims 1-3.

5. The application of the nanoparticle-induced growth of SiC nanowires as described in claim 4 in the preparation of C / C composite materials.

6. A method for preparing a nanoparticle-induced SiC nanowire-strengthened C / C composite material, characterized in that, The preform of in-situ grown SiC nanowires on the carbon fiber surface obtained in S4 of claim 1 is densified by chemical vapor infiltration through pyrolysis carbonization to obtain a nanoparticle-induced SiC nanowire-strengthened C / C composite material.

7. The method for preparing the nanoparticle-induced SiC nanowire-strengthened C / C composite material according to claim 6, characterized in that, The conditions for the chemical vapor infiltration are as follows: methane or propane is used as the carbon source gas, argon is used as the dilution gas, hydrogen is used as the carrier gas, the flow rate ratio of carbon source gas, dilution gas and carrier gas is (6-8):1:(0.2-0.4), and the total flow rate is 8-24 L / min; The deposition temperature was 1000-1080℃, the deposition pressure was 10-30 kPa, and the deposition time was 48-72 h.

8. A nanoparticle-induced growth of SiC nanowires to strengthen and toughen C / C composite material, characterized in that, It is prepared by the preparation method described in claim 6 or 7.

9. The application of the nanoparticle-induced growth of SiC nanowires as described in claim 4 or the nanoparticle-induced growth of SiC nanowires and toughened C / C composite material as described in claim 8 in the preparation of medical materials.

Citation Information

Patent Citations

  • Preparation method of catalyst-free growth SiC nanowire array and application of catalyst-free growth SiC nanowire array in biomedical materials

    CN122562542A